Strategies for flexible operation of power-to-X processes coupled with renewables. (June 2023) - Qi, Meng; Vo, Dat Nguyen; Yu, Haoshui; Shu, Chi-Min; Cui, Chengtian; Liu, Yi; Park, Jinwoo; Moon, Il
Abstract: Power-to-X (PtX) is a large-scale, long-term energy storage approach for converting renewable electrical energy into various chemical fuels. Unlike conventional fossil fuel production processes that operate continuously, PtX processes encounter operational challenges due to fluctuations in renewable power supply. To improve the operational flexibility of PtX processes for industrial applications, it is crucial to develop systematic strategies that can adapt to these fluctuations, which will increase PtX's energy and cost efficiencies. This study comprehensively explores various strategies for flexible operation of renewable-powered PtX processes, which include the use of additional energy buffers and grid connections. Power and material allocation models are developed for PtX processes based on islanded; grid-assisted; and grid-assisted, bidirectional connections by using three possible energy buffers (i.e., hydrogen intermediate storage, Li-ion batteries, and Carnot batteries). Surrogate model-based optimization is performed to establish an economically optimal design for each case. A power-to-methanol process implemented in Kramer Junction, California is studied to investigate the effects of flexible operation strategies on process performance in terms of production cost, renewable penetration, and energy efficiency. The findings of this study offer new insights into the operational flexibility of PtX processes and provide general recommendations for improving the flexibility and performance of PtX, particularly with respect to the establishment of a grid connection and the selection of an appropriate energy buffer. Graphical abstract: Image 1 Highlights: Power-to-X flexibility through various energy buffers and grid connections. Comparison of hydrogen, lithium-ion and Carnot batteries as energy buffers. Significant reduction in production costs through bi-directional grid connections. Guidelines and suggestions for choosing a flexible operation strategy.